The Effectiveness of Leadership Functions Implementation in The Makassar Departement of Manpower - Risma Niswaty; Fajriah Juniati; Muh. Darwis; Rudi Salam; Sitti Hardiyanti Arhas (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
This study aims to find out about how leadership functions implementation in the Makassar Departement of Manpower. Research design, data processing and data analysis in this researchis a descriptive approach. The techniques used in collecting data are observation, questionnaires, interviews and documentation. The results indicate the effectiveness of the implementation of the leadership function in the Makassar Departement of Manpower is quite effective.The results of the indicators, first, decision making functions and delegate functions are classified as effective;second,instructive functions, consultative functions and participatory functions are categorized quite effective. The application of the leadership function in the Makassar Departement of Manpoweris quite effective because leader is able to revive the organization with a good work climate and the leaders in the Departement of Manpowercan always be part of what their employees feel.